A Software Watermarking Based on PE File with Tamper-proof Function - Shengbing Che; Yemao Wang (Institute of Advanced Engineering and Science, 2014)
After embedding the watermark based on the algorithm of PE file resources section, the data of resource section was still easy to be rearranged, so this paper put forward a new watermark algorithm with the function of anti-tamper. The new algorithm still used watermark information to control the order of software resource structure’s nodes, and hid the watermark information in the rearranged resource structure. At the same time it recorded the exchanged node information of each layer, and encoded these exchanged nodes’ information. Then it constructed corresponding MPPCT and DPPCT according to the encoding results to achieve the purpose of anti-tamper. Experiment shows that it realizes a blind detection, resists multiple common attacks effectively, and has strong robustness. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4215